Implementation of A Career Guidance Program - Mellynda; Besti Nora Dwi Putri; Yasrial Chandra (Global Action and Education for Society, 2025)
This study was prompted by the fact that many students still struggle to determine their interests and career paths in line with their personal potential, highlighting the need for effective career guidance programs in schools. The purpose of this research is to describe the implementation of the career guidance program at SMA N 2 Bukittinggi, covering aspects of planning, service delivery, and program evaluation. This study employed a qualitative descriptive approach. The main informants were two guidance and counseling teachers, supported by the counseling coordinator, the vice principal for curriculum affairs, and two homeroom teachers as additional sources. Data were collected through interviews and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the planning was based on student needs assessments and aligned with the school’s vision, although limited by time constraints. Services were provided through classroom guidance, group counseling, and individual sessions, but not all students were equally reached. Evaluation was conducted using questionnaires, yet mostly done orally and in a simple manner. In conclusion, while the career guidance program is being implemented, it still faces several obstacles in achieving its full potential.